2015
DOI: 10.3390/ijerph120605905
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Exposure to Heavy Metals among Residents in the Industrial Complex: Korean National Cohort Study

Abstract: A survey was conducted to evaluate the multi-exposure level and correlation among toxic metal biomarkers (Cd, Pb, and Hg). A total of 592 individuals who participated in the survey were residents near an industrial complex in Gwangyang and Yeosu (exposed group) and of Hadong and Namhae (control group) in southern Korea from May 2007 to November 2010. The Gwangyang and Yeosu area exposed groups had slightly higher blood Pb (2.21 and 1.90 µg/dL), urinary Cd observed values (2.20 and 1.46 µg/L), urinary Cd with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…It is located near the Gwangyang industrial complex, which is populated by large oil refineries and petrochemical manufacturing plants [ 9 , 10 ]. A number of studies have been conducted and reported that the levels of environmental air pollution—including nitrogen dioxide (NO 2 ), carbon monoxide (CO), ozone (O 3 ), dioxins, toxic metals, volatile organic compounds (VOCs), formaldehyde, polychlorinated biphenyls (PCBs), polycyclic aromatic hydrocarbons (PAHs), and particulate matter (PM)—were significantly increasing in the atmosphere, soil, and aquatic environments in these industrial complexes, which have been most affected [ 11 , 12 , 13 ]. Several studies concluded that chronic exposure to low levels of hazardous pollutants were significantly related to adverse effects on respiratory and cardiovascular systems among the residents living closer to Gwangyang and Yeosu industrial complexes in Korea [ 12 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is located near the Gwangyang industrial complex, which is populated by large oil refineries and petrochemical manufacturing plants [ 9 , 10 ]. A number of studies have been conducted and reported that the levels of environmental air pollution—including nitrogen dioxide (NO 2 ), carbon monoxide (CO), ozone (O 3 ), dioxins, toxic metals, volatile organic compounds (VOCs), formaldehyde, polychlorinated biphenyls (PCBs), polycyclic aromatic hydrocarbons (PAHs), and particulate matter (PM)—were significantly increasing in the atmosphere, soil, and aquatic environments in these industrial complexes, which have been most affected [ 11 , 12 , 13 ]. Several studies concluded that chronic exposure to low levels of hazardous pollutants were significantly related to adverse effects on respiratory and cardiovascular systems among the residents living closer to Gwangyang and Yeosu industrial complexes in Korea [ 12 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The associations between physical geography and proteinuria’s prevalence may be related to environmental pollution exposure. The southern and eastern areas of South Korea have major industrial complexes with severe air pollution [57,58,59,60]. Combustion and industry are the most common and influential sources of PM 10 [61].…”
Section: Discussionmentioning
confidence: 99%
“…In Korea, diseases caused by the environment exposed to the occupants in the industrial complex area can occur. This has been found to affect exposure of secondary pollutants through diffusion of the atmosphere [1,2]. Depending on the characteristics of the industrial area, toxicity evaluation of human body, risk assessment and health impact assessment may directly cause cancer due to air pollution [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…High blood pressure,2 Stroke,3 Cerebrovascular,4 Angina,5 Myocardial infarction,6 Diabetes,7 Anemia,8 Thyroid disease,9 COPD, chronic obstructive pulmonary disease,10 Bronchitis,11 Pulmonary emphysema,12 Bronchiectasis,13 Asthma,14 Sinus infection,15 Allergic coryza,16 Allergy desmatitis,17 Bronchial asthma,18 Acute bronchitis,19 Pneumonia,20 Acute pneumonia,21 Skin Disease…”
mentioning
confidence: 99%